Code-switching in Chinese junior secondary school EFL classes: functions and student preferences. Issue 3 (4th May 2023) - Ye, Xuejun
ABSTRACT: In China, code-switching (CS) is frequently used in English as a foreign language (EFL) classrooms. However, the functions of CS in Chinese secondary schools remain unclear. Moreover, student perceptions have rarely been considered in previous studies. This paper therefore sets out to examine why English teachers code-switch in EFL classrooms. In contrast to other studies, this paper highlights the functions of both Mandarin and the Sichuan dialect. The perceptions of different-achieving students are then closely investigated with a view to gauging their ideal teacher CS practice. Teachers and student participants from a junior secondary school in China participated in this ethnographic study. Participants' triangulated responses revealed that CS mainly served the four major functions of knowledge construction, classroom management, relationship building, and contextual constraint accommodation. This study also provides evidence that Mandarin and the dialect served both similar and different functions in the EFL classrooms. They resemble each other in relationship building while differing in terms of other three functions. Students' varied answers reinforced the importance of providing comprehensible input and employing optimal CS use in EFL classes. The study concluded with two practical suggestions for teachers, policymakers and school leaders to better implement effective CS practice.